(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates the relationship between environmental, social, and governance disclosure and the financial sustainability of Saudi Arabian firms, while examining the moderating role of the 2017 corporate governance reforms. Using a balanced sample of 40 firms listed on the Saudi Stock Exchange results suggest that stronger environmental, social, and governance disclosure significantly enhances financial sustainability, with the effect becoming more pronounced after controlling for firm-specific heterogeneity. Corporate governance reforms are shown to amplify the positive influence of sustainability practices, underscoring the effectiveness of regulatory improvements in aligning firms with long-term stability objectives. Discretionary accruals as well as greenwashing practices results in lower financial sustainability. The study contributes, with addition to discretionary accruals, to the literature by providing evidence from an emerging market and highlights the importance of regulatory and managerial commitment to sustainable corporate practices.